Effect of Recast Cobalt Chrome Base Metal Alloy on Flexural Bond Strength of Metal Ceramic Restoration - Gibi Babu Philip; Kavan A. Patel; Liya Neha Bipinchandra; Ruchita Patel; Soniya Sara Jacob; V.H. Dhanya (Journal of Pharmacy and Bioallied Sciences)
Aim: The aim of this study was to assess and compare the outcome of recasting of CoCr alloy on the metal ceramic flexural bond strength. Materials and Methods: 50 resin patterns were fabricated and divided into 5 equal groups and casted as: Group 1 containing 0%, Group 2 containing 20%, Group 3 containing 30%, Group 4 containing 40%, and Group 5 containing 100% recast alloy. They were layered with VITA VMK 68 porcelain powder and put through to 3-point bending test using Universal Testing Machine. Data obtained was statistically analyzed using one-way ANOVA which was followed by Tukey honest significant difference post hoc test (α = 0.05). Results: A reduction in bond strength was noted as the percentage of recast alloys were increased. Group 5 showed a notable reduction (P < 0.001) in bond strength compared to other groups as it was performed on 100% recast alloys. Conclusions: Metal ceramic flexural bond strength reduced as the percentage of one-time used alloy increased. 40% of once used alloy can be considered safe to achieve optimal bond strength.